The Influence of Environment, Social, Governance (ESG) on Company Value on the Indonesian Stock Exchange - Supranata, Mardani; Marsono, Acong Dewantoro; Lailiyah, Nadhifatul (Sekolah Menengah Kejuruan (SMK) Pustek, 2025)
This study aims to analyze the effect of Environmental, Social, and Governance (ESG) on firm value in companies listed in the LQ45 Index for the period 2023. ESG has become an important factor in investment decisions, as global awareness of sustainability and corporate responsibility increases. This study uses linear regression to examine the relationship between ESG, firm size, and leverage on firm value as measured by Tobin's Q ratio. The results show that ESG and firm size have a significant effect on firm value, while leverage has no significant effect. Companies with higher ESG scores tend to have better market value, as investors see it as an indicator of better risk management and business sustainability. In addition, firms with larger size tend to be better able to adopt ESG practices effectively, which increases competitiveness and market confidence. In contrast, high leverage does not directly contribute to firm value, as the financial risks posed may hinder the implementation of sustainability strategies. The implication of this study confirms that the implementation of ESG not only increases the value of the company but also supports business sustainability in the long run. For investors, ESG can be a key consideration factor in assessing company performance and prospects. Meanwhile, for regulators and company management, these results reinforce the urgency of ESG transparency and implementation to maintain competitiveness and business sustainability.